Intertextual Links in the Context of the Problem of Folklore-Literary Relationships (with Reference to National Literature) - Abulhanova, Zilya Ravilevna; Khubbitdinova, Narkas Ahmetovna; Mingazova, Liailia Ihsanovna (Journal of History Culture and Art Research, 2017)
An attempts to apply the theory of intertextual analysis to the study of the ancient work of national literature, the Bashkir literature in particular, was made in the article. The folklore motifs used in the work mostly cause intertextual communication, an allusion to the poetic traditions of the Bashkir folklore, which are endowed with original artistic and aesthetic functions. In the frame of the article were considered the usage of the intertextual method in the study of the Turkic and Bashkir literatures, what gives a possibility to reveal the degree of correlation of works with the Eastern, Turkic-Bashkir literary and folklore traditions, to expand understanding of the semantics and poetics of literature, to define new ways of interpretation, to consider the literary heritage of the Bashkir people as an art system included in a single world context. The urgency of the work is beyond question, given that for the first time the work involves an attempt to combine traditional research methods with the theory of the intertextual analysis of a literary work.